2013
DOI: 10.1111/1755-0998.12086
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation in Cladonia (Ascomycota): a challenge to the DNA barcoding philosophy

Abstract: The lichen-forming fungal genus Cladonia is species-rich with approximately 500 described species. The accepted barcode for fungi (ITS rDNA) often fails in identifying Cladonia spp. In order to find other markers that, in combination with the ITS rDNA region can be used for species identification in Cladonia, we studied the loci IGS rDNA, ef1α, rpb2 and cox1. A total of 782 sequences from 36 species have been analyzed. PCR amplification success rate, intraspecific and interspecific genetic distance variation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 84 publications
1
55
1
Order By: Relevance
“…; Pino‐Bodas et al . ). However, none of the four chloroplast regions showed a barcode gap in our study.…”
Section: Discussionmentioning
confidence: 97%
“…; Pino‐Bodas et al . ). However, none of the four chloroplast regions showed a barcode gap in our study.…”
Section: Discussionmentioning
confidence: 97%
“…For lichens a composite tree ( Figure B2) was created manually and adjusted according to recently published phylogenies (Helms et al 2003, Schmull et al 2011, Prieto and Wedin 2013 studies of the Cladoniaceae family (Stenroos 2002, Fontaine et al 2010, Pino-Bodas et al 2013 were included. No phylogenetic analysis was available for some species of the genus Cladonia: Cladonia bellidiflora, C. glauca and C. ramulosa.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…In fungi, several regions have been utilized for phylogenetic studies including the ITS, 28S-LSU, and 18S-SSU of the rRNA cistron regions, as well as CO1 ( Penicillium ), MCM7 (ascomycetes), and RBP1 (Assembling the Fungal Tree of Life, AFToL project) [45], [58], [66]. Schoch et al recently reported that the ITS region was generally superior to the LSU in species discrimination and had a more clearly defined barcode gap, indicating that the ITS region should be designated as the universal barcode for fungi [45].…”
Section: Discussionmentioning
confidence: 99%